Spregledani potenciali odprtega prostora mesta - novi tipi in kategorije mestne pokrajine - Šuklje Erjavec, Ina (Urbani izziv, 2001)
Cities possess numerous overlooked and underutilised potential spaces for organising green surfaces and open urban spaces. They are defined by their position in the city, adequate contents nearby that could attract visitors andactual availability of space. The article presents some of the most typicaloverlooked potentials, such as: schools, kindergartens, homes for the elderly, open spaces and green surfaces adjacent to public institutions, localand neighbourhood centres, large shopping centres, industrial buildings etc. In conclusion certain proposals for new types of spaces in the urban landscape are presented, spaces that could improve the quality of life in cities.
Keywords: krajinska arhitektura; mesta; mestni predeli; parki; prostorsko urejanje; zelene površine; zelenice